Formative assessment in Timor-Leste: teachers’ perception and practice - Costa Akoyt, Melky (International Journal of Educational Innovation and Research, 2024)
Formative assessment is vital in many educational contexts because it helps improve students' learning outcomes. Like many other countries, Timor-Leste education promotes formative assessment alongside other educational assessments. Yet, the use of formative assessment in Timorese classroom is still a subject of inquiry. This study aimed to investigate Timorese teachers' perceptions and practices of formative assessment in the classrooms and examine their differences. The sample was drawn from 50 teachers working in 14 primary schools within Dili municipality. The data was gathered through a questionnaire survey. The questionnaire consisted of demographic information, teachers' perceptions, and their practices. The results showed that many Timorese teachers had positive perceptions of formative assessment. They knew the importance and the role of formative assessment for learning. However, the teachers' practices of formative assessment differed from their perceptions. Most teachers rarely apply formative assessment and its various strategies in their classrooms. This research suggests that relevant government bodies, such as the Ministry of Education, must consider the importance of educational qualifications and continuous professional development programs. Large class sizes and the lack of internal school support also become essential aspects that need attention from the government. The findings of this research provided insights that can be incorporated into the existing literature and serve as the basis for further research in the Timorese education context, particularly in primary education.